Youth Politeness in Podcasting: Two Costa Rican Cases - Picado Madrigal, Karla (2025)
Politeness is examined in two podcasts of young Costa Ricans, considering their speech acts and courtesy strategies. This analysis is based on the postulates of Brown and Levinson on the theory of politeness strategies, and the perspective of speech acts proposed by Searle. The results show how positive politeness is used more than negative politeness; speakers try to conserve the positive face of their listeners, thereby preserving trust and friendship within the conversation.